Policy masquerading as science: an examination of non-state actor involvement in European risk assessment policy for genetically modified animals - Hartley, Sarah (Taylor & Francis, 2015)
In 2013, at the request of the European Commission, the European Food Safety Authority (EFSA) announced a new risk assessment policy: Guidance on the environmental risks of genetically modified (GM) animals (‘Guidance’). This policy specifies the issues to be addressed in future risk assessments for GM animals. EFSA is the European Commission's scientific arm, responsible for food-related risk assessment. EFSA relies heavily on independent experts and consults non-state actors. Employing expert interviews and documentary analysis, the article explores non-state actor involvement in a traditionally expert domain through a case study. Analysis of EFSA's consultation demonstrates the inability of non-state actors to influence policy. The article argues that despite international legal obligations to develop risk assessment policy, the European Commission failed to recognize the Guidance as policy. When policy masquerades as science, unjustified restrictions are placed on non-state actor involvement and value judgements are cloaked from public scrutiny.